2013
DOI: 10.1002/cctc.201300006
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite Catalyzed Transformation of Carbohydrates to Alkyl Levulinates

Abstract: Caught in an acid trap! Zeolites with moderate acidity are demonstrated to be versatile and reusable solid‐acid catalysts for the transformation of biomass derived carbohydrates to alkyl levulinates in alcohol solvents. In short‐chained alcohols it proved possible to obtain significantly higher yields of alkyl levulinates, than what is achievable of levulinic acid in analogous reactions performed in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
109
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 35 publications
6
109
0
Order By: Relevance
“…Zeolite beta and its modified versions are known to be effective catalysts for several reactions concerning the valorisation of biomass, e.g. corn fiber to Fur [38]; levuglucosan (an intermediate of (hemi)cellulose pyrolysis) to glucose [39] or Fur [40]; saccharides to Fur [41,42], 5-(hydroxymethyl)furfural (HMF) [42][43][44][45][46][47], or LEs [48,49]; cellulose and hemicelluloses to diesel [50]; hemicelluloses to polyols [51]; C-3 sugar to methyl lactate and lactic acid [52]; FA to 2-(ethoxymethyl)furfural (EMF) and ethyl levulinate (EL) [53]; biodegradable surfactants via acetalisation [54] or etherification of HMF [55]; Fur to GVL [4]; pyrolysis of biomass or derived compounds to aromatic/aliphatic 4 hydrocarbons [56][57][58][59][60][61][62][63][64][65][66]; sugarcane bagasse to bio-oil and upgrading to fuel [67]; co-conversion of biogenic waste and vegetable oil [68]; and pyrolysis of organosolv lignin to phenolic compounds [69,70]. The introduction of different elements into zeolite beta widens its catalytic potential.…”
Section: Introductionmentioning
confidence: 99%
“…Zeolite beta and its modified versions are known to be effective catalysts for several reactions concerning the valorisation of biomass, e.g. corn fiber to Fur [38]; levuglucosan (an intermediate of (hemi)cellulose pyrolysis) to glucose [39] or Fur [40]; saccharides to Fur [41,42], 5-(hydroxymethyl)furfural (HMF) [42][43][44][45][46][47], or LEs [48,49]; cellulose and hemicelluloses to diesel [50]; hemicelluloses to polyols [51]; C-3 sugar to methyl lactate and lactic acid [52]; FA to 2-(ethoxymethyl)furfural (EMF) and ethyl levulinate (EL) [53]; biodegradable surfactants via acetalisation [54] or etherification of HMF [55]; Fur to GVL [4]; pyrolysis of biomass or derived compounds to aromatic/aliphatic 4 hydrocarbons [56][57][58][59][60][61][62][63][64][65][66]; sugarcane bagasse to bio-oil and upgrading to fuel [67]; co-conversion of biogenic waste and vegetable oil [68]; and pyrolysis of organosolv lignin to phenolic compounds [69,70]. The introduction of different elements into zeolite beta widens its catalytic potential.…”
Section: Introductionmentioning
confidence: 99%
“…However, both levulinic acid and furfuryl alcohol need to be prepared from carbohydrates or biomass firstly, and then need to be purified for synthesis of ethyl levulinate. In addition, there is a third route for synthesis of ethyl levulinate that is to be converted from carbohydrates or biomass directly [14][15][16][17]. This route provides a convenient one-pot reaction to produce ethyl levulinate.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Saravanamurugan et al reported a selective synthesis of methyl levulinate from monosaccharides using several zeolites [38]. As shown in Table 7, as the Si/Al ratio increased, the Brønsted acidity was reduced, and the yield of the desired product was lowered.…”
Section: Production Of Alkyl Levulinates From Carbohydrates Using Hetmentioning
confidence: 99%